A comparative study on the benefits offered to faculty in private and public educational institutions - K Vanishree; Sharma Ankita; Mandava Vaishnavi; BH Kushal (ITM Web of Conferences)
This study aims to explore the quality of work life (QWL) for university teachers in Bangalore’s private sector. The purpose of this study is to evaluate the quality of work life (QWL) of private-sector teachers, compare it with their public-sector counterparts, and explore any potential benefits that public-sector employment might offer. A personal interview with a structured questionnaire was conducted with 100 teachers in Bangalore’s private sector. Data was analyzed with a T-test. Results indicate that while private sector teachers enjoy comparable professional development opportunities, they face challenges in work-life balance and lack non-financial incentives compared to public sector colleagues. These disparities create a stressful environment for private-sector teachers, potentially impacting their job satisfaction and student performance. The findings of this study advocate for reducing disparities between the public and private education sectors, adding to the ongoing dialogue between employees and employers in the educational sector. Additionally, the study aims to inform policymakers to foster a more equitable environment across the educational space. The findings of this study aim to inform policymakers in fostering a more equitable environment across the educational space by reducing disparities between the public and private education sectors. It also contributes to the ongoing dialogue between employees and employers in the educational sector.